Study on anisotropies and momentum densities in AlN, GaN and InN by positron annihilation - Amrane, N.; Benkraouda, M.; Qamhieh, N.; T. Mahmoud, Saleh (JOURNAL OF ADVANCES IN PHYSICS, 2016)
The independent particle model (IPM) coupled with empirical pseudopotential method (EPM) was used to compute the thermalized positron charge densities in specific family of binary tetrahedrally coordinated crystals of formula ANB8-N. Initial results show a clear asymmetrical positron charge distribution relative to the bond center. It is observed that the positron density is maximum in the open interstices and is excluded not only, from the ion cores but also to a considerable degree from the valence bonds. Electron-positron momentum densities are calculated for the (001,110) planes. The results are used to analyze the positron effects in AlN, GaN and InN compounds. Our computational technique provides the theoretical means of interpreting the k-space densities obtained experimentally using the twodimensional angular correlation of annihilation radiation (2D-ACAR).